The Impact of Basic Education Curriculum Gaps on Meeting Tertiary Education Admission Criteria – A Case of South Africa - Zona Ndamase; Mohammed Xolile Ntshangase (Journal of Education and Learning Technology)
Access to higher education is often hindered by curriculum gaps in secondary education, where misalignment between school curricula and university admission requirements leaves many students underprepared and ineligible for their desired programs. This qualitative study set out to explore ways in which curriculum gaps negatively impact students’ ability to meet admission criteria, aiming to highlight systemic challenges and propose solutions to bridge the divide between secondary and higher education. 4 teachers, 2 university administration officers, and 4 learners who seek entry into the university from different high schools were purposively sampled for semi-structured interviews and focus group interviews, and the data were thematically analysed in this study. The Critical Social Theory served as the lens through which this whole discussion in this study was addressed. The study identified significant misalignment between high school subjects and the prerequisites for tertiary education programs, particularly in STEM and professional fields. The study revealed that a lack of guidance on subject selection and inadequate preparation for standardised assessments further compound the problem, leaving students ill-equipped to meet competitive admission criteria. It is recommended that stakeholders address curriculum gaps that require systemic reforms, including aligning secondary education content with university requirements, improving career guidance, and equipping schools with adequate resources. These measures will ensure that all students have equal opportunities to access higher education and pursue their career aspirations regardless of background. The study contributes to existing literature on improving equitable access to higher education opportunities by addressing this issue.